Causes of mortality in military working dog from traumatic injuries - Storer, Amanda P.; Edwards, Thomas H.; Rutter, Christine R.; Young, Grace E.; Mullaney, Sara B. (Frontiers in Veterinary Science, 2024)
Introduction This study aimed to identify the pathophysiologic causes of death following traumatic injuries in military working dogs (MWDs) and determine the risk factors associated with mortality in MWD following traumatic injuries. The results of this study will allow for better targeting of interventions to ameliorate these pathophysiologic causes of death and inform research priorities directed at the pathophysiology that leads to the death of MWDs. Methods The final dataset for this study was compiled by using two previously established datasets. Based on review of available data and supplemental records (when available), MWDs in which a definitive cause of death could be determined were included in the study population. These MWDs were assigned a cause of death based on categories previously identified in studies evaluating service member casualties. A group of MWDs who survived their traumatic injury and had similar mechanisms of injury and types of injury to the deceased MWDs were included to allow for comparison and establishment of risk factors associated with MWD death. Variables collected included breed, age, sex, mechanism of injury, survival/non-survival, type of trauma, mechanism of injury, pathophysiology that led to death and pre-hospital care provided. Statistical analysis included Fishers exact test for categorical variables and univariable and multivariable logistic regression to identify factors associated with the MWD death. Results A total of 84 MWDs (33 non-survivors and 51 survivors) were included in this study. Of the 33 MWDs that died, 27 (81.8%) were noted to be dead on arrival. The pathophysiologic causes of death were found to be hemorrhage (45.5% [n = 15]), head trauma (21.2% [n = 7]), catastrophic tissue destruction (15.2% [n = 5]), pneumothorax (9.1% [n = 3]) and one (3% [n = 1]) of each of the following: septic shock, asphyxiation and burns. Military working dogs that did not receive non-DVM care were 3.55 times more likely to die than those that did receive non-DVM care (95% CI 1.03–12.27). The majority of MWDs died of their injuries before reaching veterinary care. Discussion To increase the survival of MWDs on the battlefield, further research should focus on developing new interventions and techniques to mitigate the effects of the pathophysiology noted to cause MWD death. Furthermore, given that care by a non-DVM was found to be associated with survival, the implementation of pre-hospital care and early resuscitation techniques should be a continued priority for those treating MWDs at both the point of injury and in the prehospital setting.